IMPLEMENTASI KEBIJAKAN PROGRAM FORUM ANAK DALAM PENCEGAHAN PERNIKAHAN ANAK DI KABUPATEN BREBES: - Hakim, Muhammad Fadhillah; Sutjiatmi , Sri; Habibullah, Akhmad (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Child marriage remains a significant problem in Brebes Regency and is a contributing factor to the annual population increase. The Children's Forum program, managed by the DP3KB (Children's Forum), is a local government effort to reduce child marriage cases. It utilizes George C. Edwards III's policy implementation theory, which encompasses factors such as communication, resources, disposition, and bureaucratic structure. Qualitative descriptive methods were used in the study through observation and interviews. The results show that the Children's Forum serves as an example by conducting outreach activities in schools, educating students about the risks of child marriage, and collaborating with the DP3KB. Over the past five years, the program has helped reduce the percentage of early marriages under the age of 17. However, issues such as cultural factors, a lack of parental digital literacy, and a short-term mindset persist. Therefore, the Children's Forum has demonstrated successful policy implementation; however, to improve prevention outcomes, programs such as parenting classes should be implemented to make child marriage prevention more effective.